La naturaleza teológica del momento inductivo En tiempos de diversidad, pluralismo y alteridad cultural - Schickendantz, Carlos Federico (Veritas, 2017)
The hermeneutical structure of Gaudium et Spes, grounded in the see-judge-act method, was the subject of arduous debates during the Second Vatican Council. The influence of the method after the Council has been vital for the Church throughout the world, particularly upon the theological and pastoral work done in Latin America. The present article offers an analysis of recent contributions that aim at enhancing the method, especially when auscultating and intentionally listening to reality. It highlights some proposed developments and underlines enduring convictions. Most importantly, it calls for the exploration of a more theological reading of reality that demands a change in the way revelation is envisioned and understood, and empowers theology to face and assume the challenges of the so-called third Illustration (diversity, cultural pluralism, otherness). (English)